Pesantren Strategies in Anti-Bullying Education and Protection of Students in Pesantren - Junaidi, Junaidi; Sahrandi, Akhmad (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2025)
Bullying among school-aged children is a global issue that threatens the mental health, safety, and social development of students. This phenomenon also occurs in Islamic educational institutions such as Islamic boarding schools, including Al Ma’ruf Islamic Boarding School in Kediri City, which ideally should be a safe space for character and spirituality building for students. This study aims to examine the individual and school environmental factors that influence the effectiveness of teachers’ strategies in preventing and handling bullying, as well as to explore how anti-bullying education is integrated into learning activities and communal life in Islamic boarding schools. Using a descriptive qualitative approach, data were obtained through non-participatory observation, in-depth interviews, and documentation studies. Research informants included madrasah leaders, teachers who were members of the violence prevention team, and students who had experienced bullying. The results showed that bullying in Islamic boarding schools mostly took the form of verbal abuse, such as teasing or insults, while physical acts were relatively rare. However, the emotional impact remained and had the potential to create a cycle of bullying if not handled properly. The Islamic boarding school implemented humane resolution measures, such as mediation, personal dialogue, emotional approaches, and character building through the example set by the ustadz. Efforts to integrate anti-bullying values were carried out through learning, orientation activities, moral training, and teacher training. The research findings emphasize the importance of collaboration among all stakeholders to create a safe, inclusive, and violence-free pesantren environment. This study contributes to the development of a character education model that is responsive to the issue of bullying in Islamic educational institutions.